ANALISIS POTENSI BAHAYA KERJA MENGGUNAKAN METODE HAZARD IDENTIFICATION RISK ASSESMENT AND RISK CONTROL (HIRARC) DI PT SUMBER MAS INDAH PLYWOOD - Novita Lisdawanti; Elly Ismiyah; Efta Dhartikasari (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
The era of industrial globalization 4.0 implements a computerized production system automatically so that not many workers will operate production machines. Every business activity must have a risk of work accidents. PT. Sumber Mas Indah Plywood is one of the successful companies characterized by export-oriented product income in 5 major countries. With the level of demand that has spread to various countries, the company must always improve the quality of the products produced. The higher the level of productivity of a company, the greater the danger or risk of work that will be posed. The purpose of this study is to conduct an analysis process consisting of hazard identification, risk assessment and risk control using hirarc method. The results showed that there are 3 work stations. In rotary stations there are 4 work activities, at dryer station there are 3 work activities and at repair stations there are 1 work activities. The results of the identification of potential hazards using hirarc method identified there are 10 potential hazards, where there is 1 potential danger including extreme risk level, 6 potential hazards including high risk level, 2 potential hazards including moderate risk level and 1 potential hazard included low risk level.